THE APPLICATION OF SPIRITUAL COUNSELING TO OVERCOME GENERALIZED ANXIETY DISORDER (GAD): A CASE STUDY ON CLIENT “I” FROM GOMBAK, SELANGOR, MALAYSIA - Muhammad Fikri, Hasya (Jurnal Konseling Pendidikan Islam, 2024)
Generalized Anxiety Disorder (GAD) is a mental disorder involving excessive and uncontrollable fear, anxiety, and worry. Referring to this research, the focus of the study is related to the description of client “I”’s GAD, such as factors, symptoms, and level of GAD anxiety disorders. This research also explains how the spiritual counseling approach can overcome client “I” ‘s GAD problem based on Surah Al-Ma'arij from verses 19 to 32. Client “I” is the main source for this research. Therefore, this research was carried out in three meetings from 03 September 2023 to 10 January 2024 according to the type of research using field research with qualitative methods. The data from this research were obtained from interviews and observations and used data analysis for case studies that had been developed by Robert  K. Yin, namely pattern matching, explanation, and time series analysis. The results of the study showed that there was a significant impact on the symptoms of anxiety disorder in a client “I”. Apart from that, the GAD level of client “I” also showed a positive change from a score of 14 to a score of 11 using the GAD-7 Rating Scale. In conclusion, a systematic spiritual counseling approach guided by the verses of the Qur'an has been proven to bring positive changes and overcome Generalized Anxiety Disorder (GAD).